Bishop John Vitez and Early Renaissance Central Europe : The Humanist Kingmaker. - MATIC, TOMISLAV (Book collections on Project MUSE., 2022)
This comprehensive biography of John Vitez, an instrumental figure of the Early Renaissance, presents a complex picture of cultural, political, and religious developments in Central Europe through one man?s life. Drawing on close study of Vitez?s writings and his various political and artistic networks of influence, Tomislav Matic demonstrates the wide scope of this church leader?s involvement in late medieval Central Europe. Not only were Vitez?s writings a catalyst for the introduction of humanism across the region, he was a patron of the arts, an avid astrologer, a master diplomat, and even a kingmaker, thus central to both political and cultural developments.